Catastrophic torrential floods in Peru. stage - Durand Castro, David (2012)
Within the extraordinary variety of landscapes of the Peruvian geography, there are areas under climatic conditions characterized by a marked seasonality of rainfall, typical of regions called semiarid, where we found a dry season centered on winter, followed by a summer rainy season. This distribution of the dry pattern rainfall in winter, determines a strong constraint on the development of plant life mainly, which is reduced in the water extreme deficit to a xerophytic vegetation typical of dry regions, while in areas where the coverage steppe protective vegetation is scarce to null, the field is more exposed to the actions of the rain erosion and surface runoff that is the origin of the processes that generate the phenomena torrential, llocllas or llapanas. Under these climatic conditions, to which must be added the human actions that favor the erosive action of rain and the “arroyada” as overgrazing, pasture burning, inappropriate agricultural practices, etc.. Which increase the effectiveness of the action of rain and then the arroyada, mobilizing abundant and fine loose material first and then thicker materials respectively. There is a remarkably effective commissioning cargo of materials especially during the first rains of the wet season. A remarkable anthropic action is taking place in tropical forest areas of the eastern flank and wide sub-andina belt, where deforestation are causing catastrophic torrential flow cases like the one just a few weeks ago in the region of San Martín.